Antifungal Activity of Resveratrol Against Botrytis Cinerea Is Improved Using 2-Furyl Derivatives - Cotoras-Tadic, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P (2011)
The antifungal effect of three furyl compounds closely related to resveratrol, (E)-3,4,5-trimethoxy-?-(2-furyl)-styrene (1), (E)-4-methoxy-?-(2-furyl)-styrene (2) and (E)-3,5-dimethoxy-?-(2-furyl)-styrene (3) against Botrytis cinerea was analyzed. The inhibitory effect, at 100 ?g ml -1 of compounds 1,2,3 and resveratrol on conidia germination, was determined to be about 70%, while at the same concentration pterostilbene (a dimethoxyl derivative of resveratrol) produced complete inhibition. The title compounds were more fungitoxic towards in vitro mycelial growth than resveratrol and pterostilbene. Compound 3 was the most active and a potential explanation of this feature is given using density functional theory (DFT) calculations on the demethoxylation/demethylation process. Compound 3 was further evaluated for its effects on laccase production, oxygen consumption and membrane integrity of B. cinerea. An increase of the laccase activity was observed in the presence of compound 3 and, using Sytox Green nucleic acid stain, it was demonstrated that this compound altered B. cinerea membrane. Finally, compound 3 partially affected conidia respiration. © 2011 Caruso et al.